Exploring associations between the FTO rs9939609 genotype and plasma concentrations of appetite-related hormones in adults with obesity. - Ann Kristin Hjelle de Soysa; Mette Langaas; Valdemar Grill; Catia Martins; Ingrid Løvold Mostad (PLoS ONE)
Associations between variants in the FTO locus and plasma concentrations of appetite related hormones are inconsistent, and might not work in a dose dependent fashion in people with obesity. Moreover, it is relevant to report meal related plasma concentrations of these hormones in persons with obesity given the growing interest in their pharmacological potential in obesity therapy. We find it clinically relevant to examine associations between the SNP rs9939609 genotypes and homeostatic appetite regulation in individuals with BMI ≥35 kg/m2. This study explored associations of the rs9939609 genotypes to plasma concentrations of acylated ghrelin, active glucagon-like peptide 1 (GLP-1), and total peptide YY (PYY), and moderating effects of fat mass (FM), in 96 adults (69% female) with BMI ≥35 kg/m2, using a cross sectional observation study designed to have 1/3 of participants each with genotypes TT, AT and AA, respectively. Participants were median (25th, 75th percentile) 42.5 (32, 50) years of age, weighed 120.9 (109.6, 142.4) kg, and had a BMI of 42.8 (39.5, 46.4) kg/m2. Acylated ghrelin, active GLP-1, and total PYY were measured in the fasted state and half-hourly for 2.5h after a standardized meal. We evaluated associations between genotype and appetite hormones in regression analysis controlling for FM and sex. Genotype did not associate with fasting or postprandial (area under curve, AUC) GLP-1 or PYY. Genotype did not associate with fasting acylated ghrelin, but in females with genotype AA, increased FM was associated with higher fasting and postprandial (AUC) acylated ghrelin concentrations relative to genotypes TT (fasting p = 0.025; AUC p = 0.004) and AT (fasting p = 0.002; AUC p < 0.001). This novel finding warrants further investigation.